Modulatory Effects of Alpha-Mangostin Mediated by SIRT1/3-FOXO3a Pathway in Oxidative Stress-Induced Neuronal Cells - Ruankham, Waralee; Suwanjang, Wilasinee; Phopin, Kamonrat; Songtawee, Napat; Prachayasittikul, Virapong; Prachayasittikul, Supaluk (Frontiers in Nutrition, 2022)
alpha-Mangostin, a polyphenolic xanthone, is primarily found in the pericarp of mangosteen throughout Southeast Asia and considered as "Queen of Fruit" in Thailand. Nonetheless, it is not clarified how alpha-mangostin protects neuronal cells against oxidative stress. In this study, a molecular mechanism underlying the neuroprotective effect of alpha-mangostin in defending hydrogen peroxide (H2O2)-induced neurotoxicity was explored. Human SH-SY5Y cells were pretreated with 1 μM alpha-mangostin for 3 h prior to exposure to 400 μM H2O2. alpha-Mangostin significantly inhibited oxidative stress-induced cell death in neuronal cells by reducing BAX protein, decreasing caspase-3/7 activation, and increasing anti-apoptotic BCL-2 protein. Collectively, alpha-mangostin was demonstrated to be a prominent ROS suppressor which reversed the reduction of antioxidant enzymes (CAT and SOD2). Surprisingly, alpha-mangostin significantly promoted the expression of the sirtuin family and the FOXO3a transcription factor exerting beneficial effects on cell survival and longevity. A molecular docking study predicted that alpha-mangostin directly bound to the active site of SIRT1. Findings from this study suggest that alpha-mangostin potentially serves as a promising therapeutic compound against oxidative stress by activation of the SIRT1/3-FOXO3a pathway comparable to the effect of memantine, an anti-AD drug used for the treatment of moderate to severe dementia.